Literature Review on the Effectiveness of Kojic Acid in Reducing Skin Hyperpigmentation - Made Rendra Wisnu Rahasbistara; Angel Benny Wisan; Ida Ayu Mirah Agung (Journal of Creative Power and Ambition (JCPA), 2026)
Skin hyperpigmentation is a common condition caused by increased melanin production or distribution and can be triggered by ultraviolet light exposure, inflammation, or hormonal changes. Kojic acid is a natural compound widely used in dermatology due to its ability to inhibit tyrosinase, a key enzyme in melanin biosynthesis. This systematic literature review aims to synthesize scientific evidence regarding the effectiveness of kojic acid in reducing skin hyperpigmentation. The review was compiled following the PRISMA 2020 guidelines and searched the databases PubMed, Scopus, Web of Science, and Google Scholar. Included studies included clinical, experimental, and preclinical studies evaluating the use of kojic acid alone or in combination with other hyperpigmentation conditions for melasma, lentigo, post-inflammatory hyperpigmentation, or other hyperpigmentation conditions. Key variables extracted included study design, sample type, kojic acid concentration, duration of use, pigmentation outcomes, and side effects. In general, most studies demonstrated that kojic acid is effective in reducing hyperpigmentation intensity through tyrosinase inhibition and reduced melanin formation. This effect appears to be more consistent when used in combination with other lightening agents such as glycolic acid, hydroquinone, or niacinamide. However, skin irritation, contact dermatitis, and sensitivity may increase in some users, especially with high concentrations or prolonged use. Kojic acid shows good potential as a topical depigmenting agent for skin hyperpigmentation, but its effectiveness must be balanced against the risk of irritation and limited formulation stability. Standardization of concentration, duration, and dosage form is needed to achieve more consistent clinical benefits.